Peningkatan Kompetensi PNS Kabupaten Natuna Melalui Penyesuaian Jabatan (Inpassing) Dalam Jabatan Fungsional Tahun 2018 - Yudi Kresnasurya (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2019)
This study aims to describe and to analyze the inpassing program for functional position to support the competence development of civil servants in Natuna Goverment. This type of research used qulitative descriptive approach. Data collected was primary and secondary datas. Data collection in this study using observation, documentation, interview and literature study. Based on the analysis that just little of Natuna civil servants passed the inpassing program in 2018.